Factors Associated With a Higher Score of Burnout in a Population of 860 French Psychiatrists - Nuss, Philippe; Tessier, Cedric; Masson, Marc; Fossati, Philippe; Gaillard, Raphaël; Lapidus, Nathanaël; Gourion, David (Frontiers in Psychiatry, 2020)
Burnout rates are estimated to be twice as high among healthcare professionals as in the general working population, and studies indicate rising incidence. The present study aimed to identify the contextual factors associated with self-reported burnout rates among French psychiatrists. A total of 860 French or French-speaking psychiatrists completed an online questionnaire when they registered for a major psychiatric conference. The Copenhagen Burnout Inventory, a validated scale that independently appraises personal, work- and patient-related dimensions, was used to assess the degree of perceived burnout. Respondents were divided into lower risk and higher risk groups. The latter contained the 25% of individuals who scored the highest on each of the three dimensions of the CBI scale. Univariate analysis showed that private practice was associated with lower levels of risk on the personal and work-related dimensions. Working for the public sector and long hours were both associated with a higher score on the work-related dimension. Interestingly, none of the variables we investigated, except for poor atmosphere at work, correlated with the patient-related dimension. Among public-sector psychiatrists, female gender, longer hours, and more consultations per week were associated with a higher score on the work-related dimension. Working four or more night shifts per month was significantly associated with a higher score of burnout risk on all three dimensions. Private- and public-sector practitioners who mainly treated patients with schizophrenia had a higher score of burnout risk. Multivariate analysis showed that a poor atmosphere at work, longer hours, and working four or more night shifts were significantly associated with a higher CBI score. A non-reassuring working environment and more stressors while treating patients each had a potentially negative impact. Although this study only examined the factors that differentiated between clinicians with the lowest versus highest CBI burnout scores, it opens up important avenues for research and for the development of programs to reduce burnout risk within the French healthcare system.